A study of Inhaled Pharmaceutical Aerosol (IPA) flow characteristic with various types of fan design in metered dose inhaler - Md Tasyrif, Abdul Rahman; Ahmad Faizal; A.S., Fathinul-Syahir; Sazali, Yaacob; Hazlinda, Razali; Fauziah, Mat; Nur Saifullah; Mohd Sofian (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang Malaysia.